Blueberry polyphenols for prevention of urinary tract infection: future perspectives - Anton I. Maliavin; Lev E. Belyi (LLC "MEDIAFORMAT", 2024)
Prophylactic administration of antibiotics for urinary tract infections should be the last resort after all other preventive measures have been exhausted. This is due to the resistance of microbial flora to antibiotics, a lot of side effects of antibiotic therapy. Non-antimicrobial prevention should include the elimination of possible risk factors, behavioral modifications, as well as various options for non-antimicrobial prevention. An anti-adhesive strategy is being actively developed when various chemicals prevent the adhesion of bacteria to the urothelium. One of the variants of this strategy is the use of cranberries. Cranberries contain polyphenols with anti-adhesive potential. Other plants, representatives of the genus Vaccinium, may also be of practical interest. Blueberries are widely used in the food and pharmaceutical industries, which requires studying their phytochemical composition and anti-adhesive capabilities. Today, a significant number of in vitro studies have been conducted demonstrating both the anti-adhesive and antimicrobial potential of extracts from blueberry leaves and berries. Extracts from blueberries suppressed pathogens from urine samples, including Escherichia coli strains. Blueberry extract inhibited biofilm formation and bacterial adhesion when testing polyresistant isolates of Pseudomonas aeruginosa, E. coli, Proteus mirabilis, Acinetobacter baumannii and Staphylococcus aureus. Blueberry polyphenolic compounds inactivate E. coli and other gram-positive and gram-negative bacteria. Phytochemicals from blueberries damage the bacterial cell membrane, causing the release of protein and nucleic acids from the microbial cell, reducing the activity of some microbial enzymes. Blueberry anthocyanins can reduce the level of ATPase in the microbial cell, increasing the outflow of ATP from the cytoplasm, which has a negative effect on energy metabolism. Phytochemicals contained in blueberries can affect the transcription of genes in a microbial cell, which reduces the adaptive potential of microorganisms, and can also lead to the restoration of the sensitivity of microorganisms to certain antibiotics. There is a need for further clinical studies evaluating the effectiveness of the use of blueberries and blueberry products as an option for non-antimicrobial prevention of urinary tract infection.